Cross-cultural adaptation and search for evidence of validity of the brazilian version of the nonreligious-nonspiritual scale (NRNSS) - André Gadelha-Weyne; Ícaro Moreira Costa; Daniel Foschetti Gontijo; Tauily Claussen D´Escragnolle Taunay; Ryan Cragun (Psicologia: Reflexão e Crítica)
Abstract Background The number of non-religious people in the world has increased, which justifies the development and validation of good instruments to assess secularism, i.e., the absence of religiosity and spirituality. Objective The present study aimed to develop a cross-cultural adaptation and search for evidence of the validity of the nonreligious-nonspiritual scale (NRNSS). Methods For a congruent scale translation, a cross-cultural adaptation was performed. The search for evidence of validity was carried out through the following steps: (1) evidence of validity based on the internal structure, where an exploratory factor analysis (EFA) and confirmatory factor analyses (CFA) were performed, and the internal consistency was verified of the factors obtained; (2) evidence of validity based on converging relationships with external measurements, where correlations were made between the NRNSS factors and the Brazilian Portuguese version of the Duke Religiosity Index (P-DUREL) and the World Health Organization’s Quality of Life Instrument-Spirituality, Religion and Personal Beliefs module (WHOQOL-SRPB); and (3) comparison of self-identification categories with NRNSS outcomes using two one-way ANOVA tests, comparing scale scores between different groups (e.g., atheists, agnostics, spiritualists, and religious people). The data collection process took place through a link shared on social networks allowing access to the structured questionnaire. Results The present study obtained the following results: (1) the EFA supported a one-factor model for the scale, but (2) the CFA presented satisfactory indices for the the model composed of two factors, non-religiosity (NR) and non-spirituality (NS); (3) internal consistency indices greater than 0.95 were obtained in all factors indicated in both tested models; (4) all analyzed correlations obtained results as expected, indicating that the scale actually measures the proposed constructs; and (5) decreasing levels of NR and NS were obtained according to the respective beliefs: atheists, agnostics, spiritualists, and religious people. Conclusion The NRNSS presented favorable psychometric properties, enabling it to be used with two different factors (NR and NS).